Evaluation of formability and planar anisotropy based on textures in aluminum alloys processed by a shear deforming process - Han, Jun-Hyun; Suh, Jin-Yoo; Jee, Kwang-Koo; Lee, Jae-Chul (ELSEVIER SCIENCE SA, 2008)
The shear forming of 1050 aluminum alloys was conducted repeatedly via a shear deforming process termed dissimilar channel angular pressing (DCAP), in order to study the effect of the accumulative strain on the formability and planar anisotropy of aluminum alloy sheets. Very high plastic strains (epsilon(eff)similar to 19) were imparted to the alloys by repeated DCAP (N= 32). The finite element method (FEM) was used to analyze the deformation history during the DCAP. The corresponding texture evolution due to DCAP was simulated using the deformation history extracted from the FEM analysis. Experimental verification of the analytical results was also made. The r-value (Lankford parameter) was calculated from the measured textures using the rate sensitivity model. The effects of the texture evolution due to the multiple passages of DCAP on the formability and planar anisotropy were analyzed based on the measured (r) over bar- and Delta r-values. Herein, we report on the possible production of aluminum alloy sheets having good formability and low planar anisotropy by repeated DCAP. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: CONFINED STRIP SHEARING; PLASTIC ANISOTROPY; GRAIN-REFINEMENT; EVOLUTION; SHEET; DEFORMATION; PREDICTION; BEHAVIOR; STRAIN